ANALISIS KOMODITAS UNGGULAN DAN KONTRIBUSI PERIKANAN TANGKAP TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN TRENGGALEK (Studi Kasus Di Pelabuhan Perikanan Nusantara (PPN) Kabupaten Trenggalek - Mariyana_sari mariyana_sari; Syafrial_syafrial Syafrial_syafrial; Anthon_Efani Anthon_Efani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This research was conducted in August 2016 at Prigi Fishing Port (PPN) Prigi, Tasikmadu Village, Watulimo Subdistrict, Trenggalek Regency, East Java Province. The purpose of this research is to analyze the superior commodity of catch fishery and its contribution to PAD of Trenggalek Regency. This research uses quantitative descriptive method. Flagship commodities based on volume of production and receipt are Layang Deles fish, Lemuru, Tuna Madidihang and Como Casks. The average contribution of leading commodity of catch fishery from 2011-2015 to PAD is Layang Deles fish of Lemuru 0,9%; Tuna Madidihang 0.3% fish and Como Como fish of 0.1%.